Physical Activity Level and Dietary Pattern of Undergraduate Students of Kogi State University, Anyigba Kogi State - , Achadu Abraham Eleojo; , Umeh Chisom Charles; , Jacob Moses Anyebe (Archives of Current Research International, 2019)
Nutritional habits and physical activity influence the health status and cognition of young adults. The objective of this study was to assess the physical activity level and dietary pattern of undergraduate students of Kogi State University, Anyigba Kogi State. In this study, a group of 246 students from the university (150 female and 96 male subjects) were engaged. Ethical clearance was obtained from the Health Research ethics committee, Kogi state ministry of health and all students signed a written consent form. With the aid of a validated questionnaire, interview was conducted to obtain information on demographic and physical activity levels after obtaining informed consent from the target population. Anthropometric measurements were carried out to ascertain the nutritional status, and dietary intakes were equally assessed using a food frequency questionnaire. 27.4% and 6.4% of target population recorded low and high levels of physical activity respectively. Healthy weight was recorded at 72% and obesity at 3.7%. Despite the high percentage in healthy weight, a low physical activity level was recorded, with inadequate meal patterns and food choices. This suggests an urgent necessity for improving overall health status of students by implementing a university based nutrition and exercise awareness programme.